Preparation and In-Vitro Evaluation of Floating Oral In- Situ Gel of Montelukast Sodium (Conference Paper) # - Adnan, Manar; RoaaA.Nief,; Shaimaa Nazar Abd-Al Hameed,; Haneen Abdulhadi Kharaba, (Iraqi Journal of Pharmaceutical Sciences, 2023)
There were several goals in this study, the most important of which was to create an oral liquid preparation (Ion sensitive floating oral in situ gel system for sustained delivery of Montelukast Sodium for pediatric patients) that would make administration easier, provide the correct therapeutic dose, and allow the drug to be released more slowly into the digestive tract (GIT) for better control.Montelukast Sodium in situ gels at different concentration (w/v) of natural polysaccharides (Gellan gum and sodium alginate) and natural polymer (Pectin) were prepared and characterized in the terms of preparation, viscosity and In vitro release.As the concentrations of ion-sensitive gel-forming components (Gellan gum, sodium alginate, and pectin) and gas-generating ingredients increased, the viscosity of formulations in solution (CaCO3). In vitro release study showed that the release of Montelukast Sodium from these gels was characterized by an initial phase of high release (burst effect), followed by a more gradual release in the second phase.The oral distribution of Montelukast Sodium using the in situ gel system manufactured by Montelukast Sodium can be seen as a viable strategy for the improvement of therapeutic effects.